Simulation of the Influence of the as-Deposited Wall Thickness on Arc Shape and Stability during Wire Arc Additive Manufacturing - Chundong Zhou; Xiaoyong Zhang; Yong Peng; Yong Huang; Kehong Wang; Jianchun Wang; Ming Zhou (Metals, 2022)
The single-pass multi-layer depositing strategy is usually used to fabricate thin-wall structures with wire and arc additive manufacturing (WAAM) technology. Various deposited wall thicknesses often lead to a change in arc shrinkage in the wall thickness direction, which affects the arc shape and stability, and even the microstructure and properties. To systematically study the effect of wall thickness (δ) on arc shape and stability, 3D numerical models were established, with wall thickness varying from 1 to 14 mm during the WAAM process. The characteristics of the arc shape, temperature field, velocity field, current density, and the electromagnetic force were investigated. When δ is smaller than the arc diameter (Φ), the thinner wall will result in a longer arc along the deposition direction. When δ is greater than the Φ, the arc shape tends to be a bell shape. When δ < Φ, the peak temperature in the arc centre, the peak current density, and the electromagnetic intensity along the welding direction decreased with the increase in the wall thickness. However, the opposite observations were found when δ < Φ. The simulation results are consistent with the actual arc shape collected and showed that when δ is slightly less than Φ, the forming quality of the deposited wall is the best. The research in this paper can fill the research gap and provide a theoretical basis for the matching selection of process parameters and wall thickness in WAAM applications.